2017
DOI: 10.1097/pts.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Handoffs in Community Pharmacies

Abstract: Objectives:The aims of the study were to characterize handoffs in community pharmacies and to examine factors that contribute to perceived handoff quality. Methods: A cross-sectional study of community pharmacists in a MidwestState of the United States. Self-administered questionnaires were used to collect information on participant and practice setting characteristics. Data were analyzed using descriptive statistics and multivariate logistic regression.Results: A total of 445 completed surveys were returned (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“… 66 The study identified that almost half of the time, handoffs that occur in a CP setting are inaccurate or incomplete. 66 …”
Section: Safety: Identifying Errors and Intervening Accuracy In Dispe...mentioning
confidence: 99%
See 1 more Smart Citation
“… 66 The study identified that almost half of the time, handoffs that occur in a CP setting are inaccurate or incomplete. 66 …”
Section: Safety: Identifying Errors and Intervening Accuracy In Dispe...mentioning
confidence: 99%
“…60 61 88 One study measured handovers defined as 'exchange of information, responsibility and accountability when a pharmacist concludes a shift and another replaces them at the beginning of a new shift within the same pharmacy'. 66 The study identified that almost half of the time, handoffs that occur in a CP setting are inaccurate or incomplete. 66…”
Section: Safety: Identifying Errors and Intervening Accuracy In Dispe...mentioning
confidence: 99%